PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMP NEGERI 43 PADANG - Pertiwi, Rona (Departemen Matematika, 2024)
Proficiency in mathematical problem-solving is crucial to acquire. Nevertheless, the preliminary evaluation conducted at SMPN 43 Padang revealed that the students' aptitude was much below average. The Numbered Head Together cooperative learning approach offers a resolution to the issue. This research examined the effects of the NHT model using a Non-equivalent Posttest Only Control Group Design. The t-test yielded a P-value of 0.004, indicating that the NHT model outperforms the standard learning model in answering math problems.